Climate-driven redistribution of essential oil chemotypes in Camphora officinarum: MaxEnt-based habitat projections and conservation priorities for Southern China (2021–2080) - Hou, Chen; Jiang, Yingchao; He, Boxiang; Chen, Jielian; Wang, Minghuai; Zhong, Yonglin; Li, Bing; Lian, Huiming; Li, Yongquan; Zhang, Qian (Frontiers in Ecology and Evolution, 2025)
Camphora officinarum Nees, is a significant economic tree indigenous to southern China. Despites of previous efforts, ecological niches of C. officinarum remain unclear with few sampling and neglectance of chemotypes. In the present study, new efforts have been made to investigate the integrated C. officinarum and its four chemotypes based on 546 occurances using utilizing MaxEnt model from 2021 to 2080.The findings indicate that highly suitable regions for the integrated C. officinarum are projected to diminish between 2021 and 2080, resulting in habitat fragmentation. The climatic variables influencing this are the annual mean precipitation (bio12), the minimum temperature of the coldest month (bio6), the mean precipitation during the warmest month (bio18), and the annual mean temperature (bio1). Furthermore, the regions highly suitable for each chemotype of C. officinarum are anticipated to undergo shifts and diversification from 2021 to 2080, with the primary factors driving these changes being the maximum precipitation in the driest month (bio14) and elevation. The study proposes conservation strategies at the end, furnishing a foundation for conservation and domestication of C. officinarum in South China.